Dissidents of law : (on the 1989 Velvet Revolutions, legitimations, fictions of legality and contemporary version of the social contract) /: (on the 1989 Velvet Revolutions, legitimations, fictions of legality and contemporary version of the social contract). (2019) - Přibáň, Jiří, 1967-
No abstract available